2010
DOI: 10.1042/ba20100143
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective reduction of prochiral ketones by engineered bifunctional fusion proteins

Abstract: NADPH-dependent oxidoreductases are useful catalysts for the production of chiral synthons. However, preparative applications of oxidoreductases require efficient methods for in situ regeneration of the expensive nicotinamide cofactors. An advantageous method for cofactor regeneration is the construction of bifunctional fusion proteins composed of two enzymes, one catalysing the reduction reaction and the other one mediating the recycling of cofactors. Herein, we describe the in-frame fusion between an NADP+-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 55 publications
1
22
0
1
Order By: Relevance
“…It had been reported that the fusion of two multimeric enzyme could lead to the formation of multimeric protein network [41] which may cause steric hindrance of active domain. Soluble bi-functional enzyme compose of two multimeric enzyme have reported to form oligomers [29,42]. LeuDH and FDH in our study usually formed octamer and dimer, respectively.…”
Section: The Influence Of Peptide Linker On the Thermal Stability Of supporting
confidence: 47%
“…It had been reported that the fusion of two multimeric enzyme could lead to the formation of multimeric protein network [41] which may cause steric hindrance of active domain. Soluble bi-functional enzyme compose of two multimeric enzyme have reported to form oligomers [29,42]. LeuDH and FDH in our study usually formed octamer and dimer, respectively.…”
Section: The Influence Of Peptide Linker On the Thermal Stability Of supporting
confidence: 47%
“…3, 4). It had been reported that the fusion of two multimeric enzymes could lead to the formation of a multimeric protein network [30] and the bifunctional enzyme compose of two multimeric enzymes could form oligomers [31]. In this work, LeuDH and GDH usually form in octamer and tetramer respectively, then the implementation of GDH-R3-LeuDH could form a multimeric state which explained the enhance of stability of the fusion enzyme.…”
Section: Discussionmentioning
confidence: 64%
“…Flexible linkers are typically incorporated in cases where the fused domains require a certain degree of movement or interaction (Kim et al, 2000;Blazyk and Lippard, 2004;Jiang et al, 2005;Wang et al, 2007;Lu and Feng, 2008). Most commonly used flexible linker sequences primarily consist of Gly and Ser residues ("GS" linker) (Huston et al, 1988;Kavoosi et al, 2007;Hölsch and Weuster-Botz, 2010). (G 4 S 1 ) n is one such widely used sequence.…”
Section: Discussionmentioning
confidence: 99%